Food systems in correctional settings: a literature review and case study - Smoyer, Amy B.; Kjær Minke, Linda (World Health Organization. Regional Office for Europe, 2015)
Food is a central component of life in correctional institutions and plays a critical role in the physical and mental health of incarcerated people and the construction of prisoners’ identities and relationships. An understanding of the role of food in correctional settings and effective management of food systems may improve outcomes for incarcerated people and help correctional administrators to maximize the health and safety of individuals in these institutions. This report summarizes existing research about food systems in correctional settings and provides examples of food programmes in prison and remand facilities, including a case study of food-related innovation in the Danish correctional system. Specific conclusions are offered for policy-makers, administrators of correctional institutions and prison food services professionals,and ideas for future research are proposed.
Keywords: dept.swk

Sabbatical Leave Report: Sabbatical Spring, 2015 - Keenan, Elizabeth King (Distribution: Spring ; Social Work., 2015)
From the report: "Project title: Walking the walk or just talking the talk? An exploratory study of the ways social workers understand social work practice." The report describes the research problem, identifies three reserach questions, and discusses the project outcomes and reporting.
Keywords: dept.swk; faculty_collection; sabbatical_report

Walking the Walk or Just Talking the Talk?: An Exploratory Study of the Ways Social Workers Understand Social Work Practice - Keenan, Elizabeth King (2015)
Keywords: dept.swk; faculty_collection

Fragmented images: how can the eye see itself? A relational and intersubjective reformulation of cross-cultural therapy with cecilia - Pizzanello, Heather (Psychoanalytic Social Work, 2015)
This article discusses why it is crucial in the cross-cultural clinical encounter to practice from both Jessica Benjamin's intersubjective frame as well as relational theory when the therapist is from the dominant White culture and the client is African American. Intersubjective and relational theories are utilized to illustrate how it is in this clinical situation, however, that some therapists may find themselves avoiding the use of a more relational practice. A case illustration is presented from the lens of Winnicott's theory of object relations to convey the dynamic complexities that may impede a therapist from practicing out of these (more relational) frames and then the case is reconceptualized from both a relational and intersubjective perspective. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: Winnicott; cross-cultural therapy; dept.swk; intersubjectivity; peer-reviewed; relational practice

Home environments, memories, and life stories: preservation of estonian national identity - Rakfeldt, Jaak (Journal of Baltic Studies, 2015)
This paper examines the means by which Estonian national identity was preserved during 50years of Soviet occupation. The study upon which it is based explored such factors as family environments; memories, in the form of oral narratives; and life experiences. This research was informed by the sociocultural approach to mediated action, and it employed both quantitative and qualitative research methods. In 1993, a quota-sampling technique was used to interview a cross section of Estonian society (N=930). Descriptive statistics, and factor and multiple regression analyses were performed. Fifteen qualitative interviews were also conducted. When woven together, these personal histories create a fabric that is representative of the greater Estonian history during the occupation. The implications of these findings may reach beyond the Estonian context to further inform our understanding of the complexities and the vicissitudes of human action.
Keywords: Estonian national identity; dept.swk; life stories; social memory; song festivals; “The Singing Revolution”

Full employment as a permanent policy response to poverty - Tomczak, Stephen Monroe; Rofuth, Todd W. (Journal of Community Practice, 2015)
Rising inequality and concomitant economic insecurity and poverty is a continuing problem in the United States today. Enacting full employment policies would resolve this problem and would serve as a viable poverty reduction strategy. Using a more accurate measure of unemployment such as the Bureau of Labor Statistics U-6 measure would reveal the true unemployment rate. This article provides different strategies, historical and more recent, for enacting full employment with a living wage, particularly the enactment of a permanent national public service employment program administered by the states through the TANF Emergency Fund. Public sector employment expansion in the green or clean economy would benefit the urban unemployed the most. To achieve these ends, social workers, unions and community activists will need to collaborate. Finally, the Federal Reserve should review the history of the relationship between unemployment and inflation rates and develop a more accurate formula for attaining full employment while keeping inflation low. Copyright © Taylor & Francis Group, LLC.
Keywords: United States; dept.swk; economic inequality; emergency; employment; full employment; human; human experiment; peer-reviewed; policy; poverty; social worker; statistics; unemployment

The moderating effect of positive father engagement and accessibility on a school-based system of care intervention for mental health outcomes of children - Bernard, Stanley N; Whitson, Melissa L; Kaufman, Joy S (Journal of Child and Family Studies, 2015)
We conducted an exploratory research study looking at fathering interactions as they relate to the wraparound care given by the Partnership for Kids or PARK Project, a school-based system of care in Bridgeport, Connecticut. The questions posed by our research focused on how fathers' positive interaction measured by their levels of engagement and accessibility can moderate the effect of the school-based system of care intervention on the mental health outcomes of children with serious emotional disturbances. We found that, although not statistically significant, children's access to their father did have a moderating effect on CBCL scores for internalizing behaviors and total problems. There was very small change in CBCL scores for externalizing behaviors. Further, the moderating effect of father accessibility and father engagement had a lasting effect as a moderator through 12 months into the intervention, especially with regard to internalizing behavior scores.
Keywords: Children’s mental health; Fatherhood; Systems of care; dept.swk

Conscious and unconscious use of self: the evolution of a process - Schneider, Dana A; Grady, Melissa D (Psychoanalytic Social Work, 2015)
Recent emphasis has been placed on the central role of the therapeutic relationship in successful treatment. One aspect of the development of an effective relationship is the clinical social worker's use of self. We argue that the use of self happens both consciously and unconsciously and is a dynamic and evolving process in psychotherapy. This evolution can result in the clinical social worker shifting from a stance of doing to being. Drawing from a Japanese tradition of learning, three stages of learning provide a framework for understanding how therapists may transition from a state of doing to being in the therapy. Through this process, the conscious use of self may develop into unconscious use of self. Two case examples demonstrate how expanding and using one's self-awareness and the new knowledge through meaningful learning experiences can shift a clinical social worker's ability to develop and enhance his or her use of self, inviting therapeutic presence and depth. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: conscious; dept.swk; peer-reviewed; therapeutic presence; therapeutic relationship; unconscious; use of self; way of being

“It's the black girls that have the most”: foodways narratives and the construction of race in a women's prison - Smoyer, Amy B (Food and Foodways, 2015)
Prison foodways narratives can expand knowledge about cultural beliefs and perceptions of correctional systems. This exploratory analysis, based in qualitative interview data, seeks to initiate dialogue about the ways in which formerly incarcerated women in the US deploy racialized food narratives when describing the acquisition, preparation, and consumption of prison food. The participants’ food narratives construct prison as a non-white space that is better matched for African-American and Latina women, reinforcing and enacting larger cultural notions about incarceration. This opening analysis calls for more research and deliberation about how prison foodways narratives contribute to understandings about and perceptions of correctional systems and incarcerated people. © 2015, Taylor & Francis Group, LLC.
Keywords: dept.swk